Productivity and sustainability assessment of dry direct seeded upland rice in the central mid-hills of Nepal - Bhattarai, Rajendra Kumar; Adhikari, Bishnu Bilas; Amagain, Lal Prasad; Paudel , Mina Nath; Ranjit, Jagat Devi (Nepal Agriculture Research Journal, 2025)
The dry direct-seeded upland rice is locally known as Ghaiya Dhan, is a crucial crop for food security in the hills of Nepal. However, its cultivation area and production have declined sharply over the past decade due to various biotic and abiotic stresses. A field study was conducted in the spring season 2023 across four central mid-hill districts like Dhading, Gorkha, Tanahu, and Sindhupalchowk. The findings reveal that the smallholder farmers and ethnic minority communities are found predominantly engaged in upland rice production with  average field size ranged from 0.10 ha (Sindhupalchowk) to 0.24 ha (Tanahu) with an overall average of 0.15 ha. The field preparation predominantly involved three rounds of ploughing using local tools with seed sowing through broadcasting method @ 80–100 kg seed per ha. A total of 16 rice varieties were cultivated by the farmers including 13 local landraces (Tauli (15%) and Chobo (13.3%), and 3 improved rice varieties where the Sukha Dhan-2 being a most common improved variety (6.7%). Approximately 70% of farmers applied organic manures for crop nutrition. The major constraints identified were weed infestation (41.7%), soil moisture stress (13.3%), and low productivity (8.3%). The five most problematic weeds were Cyperus rotundus, Cynodon dactylon, Echinochloa colona, Ageratum houstonianum, and Digitaria sanguinalis. The key pests included were stem borer and rice gundhi bug, while rice blast and brown spot were the predominant diseases. The grain yields were found low, ranging from 1.6 to 2.8 tons per hectare which is primarily due to above mentioned constraints and the use of low-yielding varieties. The grain nutrient analysis report revealed that the local landraces possess superior nutritive value, with higher crude protein (12.34 %) and calcium (99.01 mg) content compared to popular improved varieties (10.63 % and 71.03 mg). These findings highlight the need for targeted interventions to improve upland rice productivity and sustainability for ensuring continued food security in the hilly regions of Nepal.